The characterization of Apis cerana and Apis mellifera mrjp2 gene in Indonesia and the phylogeny relationship with mrjp family genes: Karakterisasi gen mrjp2 Apis cerana dan Apis mellifera di Indonesia dan hubungan filogeni dengan gen mrjp famili - Shullia, Nurul Insani; Febiriani, Tia Vina; Raffiudin, Rika; Widjaja, Candra; Atmowidi, Tri (Jurnal Entomologi Indonesia, 2024)
The major royal jelly protein 2 (mrjp2) gene is one of the molecular markers that can discriminate between Apis cerana Fabricius and A. mellifera Linnaeus. Due to the lack of mrjp2 gene sequences registered in GenBank for Indonesian A. cerana and A. mellifera, DNA characterization and bioinformatics analysis were needed. This research aimed to characterize the exon-intron organization of mrjp2 genes for both Indonesian bee species and analyze the phylogenetic relationship with other mrjp family genes. DNA samples of Apis cerana and A. mellifera, collected from Bogor, were amplified using MF-MR primer at annealing temperatures of 47 oC and 50 oC, respectively. The length of A. cerana and A. mellifera DNA sequences were 579 and 597 bp, respectively. The DNA sequences of both species were comprised of partial exons 1, introns 1, exons 2, introns 2, and partial exon 3. The number of putative amino acids of A. cerana and A. mellifera mrjp2 genes were 111 and 123, respectively. We confirmed that the partial MRJP2 putative amino acids of both honey bees belong to the MRJP family and contained the peptide signal in the 14 first amino acid sites. Nucleotide variation of the mrjp2 gene in A. cerana was higher than A. mellifera. Phylogenetic tree construction showed that A. cerana and A. mellifera form a monophyletic clade with the A. mellifera mrjp7 gene and another mrjp family gene clustered as reported in a previous study.